2020
DOI: 10.31557/apjcp.2020.21.10.2895
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Toward Human Papillomavirus Infection and Vaccination among Thai Women: A Nationwide Social Media Survey

Abstract: Objectives: This study was performed first to assess Thai women's knowledge and attitude toward Human papillomavirus (HPV) infection and vaccination and second to find out factors associated with knowledge in this regard. Methods: The survey announcement was advertised via Facebook from 17 May 2019 to 14 June 2019 to recruit women aged 18-26 years living in Thailand. A score below 5 out of total score of 10 on the survey was considered as a poor level of knowledge. Multivariate analysis was applied to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…To provide a more specific assessment, we developed 16 statements regarding misconceptions about cervical cancer based on a previous study, as shown in Table 3 [6,30]. The app with content that matches a specific statement receives 1 point for each content that matches the specific statement.…”
Section: App Rating Using Specific Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide a more specific assessment, we developed 16 statements regarding misconceptions about cervical cancer based on a previous study, as shown in Table 3 [6,30]. The app with content that matches a specific statement receives 1 point for each content that matches the specific statement.…”
Section: App Rating Using Specific Statementsmentioning
confidence: 99%
“…The level of knowledge of cervical cancer is associated with the success of cervical cancer programs [3][4][5]. A recent nationwide social media survey in Thailand found that nearly half of Thai women have insufficient knowledge regarding cervical cancer, indicating the need for further health education intervention [6].…”
Section: Introductionmentioning
confidence: 99%
“…A study was conducted at rural Philippines in 2020 among the community which inferred that only 13.9% underwent cervical cancer screening [7]. In a study conducted among Thai women in 2020, 46% of the participants were found to have poor knowledge regarding HPV infection and HPV vaccination [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, there was a signi cant association between the level of education and the mean score of knowledge in both studies. A recent study reported that 46% of the participants had a poor HPV and its vaccine knowledge in Thai women (14). Overall, knowledge about HPV in developing countries is low and more efforts are needed to improve the related knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the rate of vaccinated individuals is very low due to the limited information among the societies, especially in developing countries (14). There are three types of HPV vaccine, Quadrivalent vaccine (Gardasil: against HPV types 6, 11, 16, 18), Bivalent vaccine (Cervarix: against HPV types 16, 18), and 9valent vaccine (Gardasil 9: against HPV types 6, 11,16,18,31,33,45,52,58), which are all desirable to apply before sexual activity initiation (15,16).…”
Section: Introductionmentioning
confidence: 99%